THE INFLUENCE OF ESSENTIAL OILS ON THE PROPERTIES OF BIOPOLYMER FILMS BASED ON WILD FLAX (CAMELINA SATIVA) - Šuput, Danijela; Ločar, Biljana; Hromiš, Nevena; Popović, Senka; Rakita, Slađana; Spasevski, Nedeljka (Journal on Processing and Energy in Agriculture, 2024)
The aim of this work was the activation of biopolymer material based on wild flax cake (Camelina Sativa) with eucalyptus and rosemary essential oils added in different concentrations (0.5%, 1% and 2%). The wild flax cake, left over after the cold pressing of the oil, was used to obtain biopolymer films. To obtain active packaging, essential oils were added to this biopolymer material and the influence of the addition of essential oils on the physico-chemical, mechanical, barrier and biological properties of biopolymer films based on wild flax cake was examined. The obtained results showed the most significant influence on water vapor permeability. The control sample had a water vapor permeability value of 5.43 g/m2h, while in the sample with 2% added eucalyptus essential oil, this value was 3.14 g/m2h. Antioxidant activity was also confirmed in the control sample without added essential oils (60.10%), but with the addition of 2% eucalyptus essential oil, this value increased to 78.54%. Eucalyptus essential oil proved to be more effective than rosemary oil on the investigated properties of the films. The addition of essential oils to biopolymer films broadens the spectrum of functional properties, including the improvement of mechanical, barrier and biological properties.